Personality-guided cognitive-behavioral therapy - Rasmussen, Paul R. (Personality-guided psychology / series editor Theodore Millon, 2005)
(from the create) The current volume emphasizes the adaptive value or purpose of the emotional experiences defining the clinical conditions. Thus, the clinical condition, rather than being the problem, is the logical outcome of the individual's personality attributes given situational demands. The specific goal of this volume is to present the value of a theoretical model that emphasizes clinical conditions in relation to their evolutionary adaptiveness as reflected in clients' personalities. This model will be helpful for students learning to conceptualize clinical cases and to practitioners devising treatment strategies. The model should (a) enhance practitioners' understanding of clients and the contributions of clients to their own clinical conditions, (b) improve selection of appropriate interventions, and (c) optimize therapeutic benefit in minimal treatment time.